Pemanfaatan Linktree Sebagai Media Pembelajaran PAI Untuk Meningkatkan Pemahaman Zakat Bagi Siswa Kelas 6 SD - Ani Nur Aeni; Alya Arifah Marhamah; Elza Alida Yasmin; Puti Ageng Ambunsuri (Departement of Mathematics Education, 2023)
Technological developments have had a huge impact on the world of education. Technological developments require innovation in learning, so that technological advances must be utilized as well as possible by educators. The use of technology in the learning process is a must so that the learning process is not stagnant and rigid. Islamic religious education learning innovations must be carried out immediately, especially in learning methods. The research method used is Design and Development (D&D). The purpose of this study is to utilize the Linktree website for 6th grade elementary school students to deepen their understanding of zakat and can access it anywhere. The RuBelDig YuKiZa learning media (Yuk Kita Zakat Digital Learning Room) designed by utilizing the Linktree application can be an alternative method of learning zakat so that the learning process is more interesting and not boring. Ease of accessing Linktree is important for teachers and students so that Linktree can be accessed when learning is taking place or not in the school environment. With Linktree, understanding about zakat is easier to disseminate, not only in the teaching and learning process so that it can be used as well as possible. Based on this research, students understand more about zakat and teachers can use Linktree as a learning medium in class. In addition, teachers are increasingly interested in Linktree and are increasingly motivated to create interesting learning media for students with the technology that has developed.